The Moderating Role of Leverage in the Relationship Between Capital Intensity and Tax Avoidance - Arda, Devid Putra; Yusuf, Yusuf (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study investigates the influence of leverage and capital intensity on tax avoidance in companies within the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The population comprises 98 companies, from which a purposive sampling method was applied based on specific criteria, yielding 25 companies and 121 firm-year observations after excluding outliers. Secondary data were obtained from annual reports published on the IDX’s official platform. Data analysis was conducted using SmartPLS, incorporating measurement and structural model assessments to evaluate the proposed hypotheses. The results reveal that leverage has a significant positive effect on tax avoidance, whereas capital intensity shows a negative but insignificant impact. This research enriches the empirical literature on tax avoidance determinants in emerging markets and offers insights for policymakers and corporate governance to design effective strategies in reducing aggressive tax planning practices in the primary consumer goods sector.